Evolution of Sensory Properties of Beef during Long Dry Ageing - Ellies-Oury Marie-Pierre; Grossiord Benoit; Denayrolles Muriel; Papillon Sandrine; Sauvant Patrick; Hocquette Jean-François; Aussems Emmanuel (Foods, 2022)
Ageing is an essential step in obtaining meat with satisfactory sensory properties. Dry-ageing, although being a niche practice, is increasingly being developed to enhance the taste experience of meat consumers. In this work, we studied the kinetics of the evolution of muscle properties with increasing ageing time, in order to propose an optimal duration, allowing a compromise between quality and meat weight loss reduction. Our study was performed on 32 samples from 8 animals for which the Longissimus thoracis sensory properties were analysed at different stages of ageing (7, 16, 35 and 60-days post-slaughter). This work showed an increase in the dry matter content of meat with increasing ageing duration, concomitant with a slight increase in pH. Although the luminance of the meat is stabilized after 14-days, the red and yellow indices decrease until 35-days of ageing. Iron content also decreases with ageing duration. Finally, the kinetic evolution of muscle rheological properties indicates that the toughness decreases at least up to 35-days on raw meat. Cooking seems to homogenise the tenderness of the samples, no difference was noticed between the different ageing durations when meat was cooked. These first experimental data need to be confirmed with different animal types.